A Synoptic Overview of Neurovascular Interactions in the Foot - Balasubramanian, Gayathri; Vas, Prashanth; Chockalingam, Nachiappan; Naemi, Roozbeh (Frontiers in Endocrinology, 2020)
Diabetes is a worldwide public health concern as it is associated with various complications. One of the major complications of diabetes is diabetic foot syndrome that results in catastrophic events such as ulceration and amputation. Therefore, the main four strategies of diabetic foot care involve risk prediction, prevention, early diagnosis and prompt intervention. The drivers of ulceration are multifactorial, and importantly, include microcirculatory changes in the diabetic skin. Cutaneous microcirculation on the foot is greatly influenced by the small fibres which mediate thermal sensation, pain perception in addition to sympathetic activities such as thermoregulation and vasodilatory responses. The interdependence between the neurovascular elements means with the loss of small fibre functions, the corresponding microcirculatory responses may be compromised. Thus, it can be hypothesised that the impairment of the microcirculation may follow the order of the corresponding small fibre nerve dysfunction or vice versa. In this review, select neurovascular investigations that measure cutaneous microcirculation are reviewed and discussed in this order of sensory loss: the loss of pain sensation, cold, warmth, touch and deep pressure. We also discuss the neurological and vascular aspects of each of these neurovascular responses. This review highlights the influence of small fibres on cutaneous microcirculation and the need for prospective studies that can determine the course of microcirculatory impairment over time. This in turn may help clarify the exact role of microcirculatory changes in the pathway of ulceration. The insights from this review can be pertinent to understand key microcirculatory disturbances and given that the microcirculatory impairment develops at an early stage, relevant interventions can be implemented to possibly reverse or regress the course of the disease. Therefore, knowledge on the neurovascular interactions aids to map the disease progression for early diagnosis and prevention of adverse complications.